A wheat 1‐FEH w3 variant underlies enzyme activity for stem WSC remobilization to grain under drought. Issue 1 (23rd September 2014) - Zhang, Jingjuan; Xu, Yunji; Chen, Wei; Dell, Bernard; Vergauwen, Rudy; Biddulph, Ben; Khan, Nusrat; Luo, Hao; Appels, Rudi; Van den Ende, Wim
Summary: In wheat stems, the levels of fructan‐dominated water‐soluble carbohydrates (WSC) do not always correlate well with grain yield. Field drought experiments were carried out to further explain this lack of correlation. Wheat ( Triticum aestivum ) varieties, Westonia, Kauz and c . 20 genetically diverse double haploid (DH) lines derived from them were investigated. Substantial genotypic differences in fructan remobilization were found and the 1‐FEH w3 gene was shown to be the major contributor in the stem fructan remobilization process based on enzyme activity and gene expression results. A single nucleotide polymorphism (SNP) was detected in an auxin response element in the 1‐FEH w3 promoter region, therefore we speculated that the mutated Westonia allele might affect gene expression and enzyme activity levels. A cleaved amplified polymorphic (CAP) marker was generated from the SNP. The harvested results showed that the mutated Westonia 1‐FEH w3 allele was associated with a higher thousand grain weight (TGW) under drought conditions in 2011 and 2012. These results indicated that higher gene expression of 1‐FEH w3 and 1‐FEH w3 mediated enzyme activities that favoured stem WSC remobilization to the grains. The CAP marker residing in the 1‐FEH w3 promoter region may facilitate wheat breeding by selecting lines with high stem fructan remobilization capacity under terminal drought.